The offering - Derting, Kimberly (Derting, Kimberly. Pledge novel., 2014)
When the negotiation of a peace agreement with the Queendom of Astonia goes awry, Charlie receives a brutal message that threatens Ludania, and it seems her only option is to sacrifice herself in exchange for Ludanian freedom. But is she walking into a trap set by Sabara, the evil former queen of Ludania?